Enterovirus detection and serotyping of fecal material collected from three children living on the outskirts of Belem city, Amazon region, Brazil, during the first 3 years of life (1983-1986) - Coutinho, Carla Rafaela Monteiro (Wiley, 2020)
In the current investigation, fecal material was obtained during a community?based longitudinal study conducted from 1983 to 1986. This study consisted of 71 children aged newborn to 3 years. A total of 216 samples from three of these children were screened by real?time quantitative polymerase chain reaction (RT?qPCR) for the presence of enteroviruses, and positive samples were serotyped by VP1 and VP3 sequencing of the viral genome. Of these, 12 (5.6%) came from symptomatic cases, and the remaining asymptomatic cases were collected fortnightly during the 3 years of study. A positivity of 63.4% (137/216) was obtained by RT?qPCR, with 58.3% (7/12) in relation to the symptomatic group and 63.7% (130/204) in relation to the asymptomatic group. The 137 positive samples were inoculated into the RD, HEp2C, and L20B cell lines, and the cytopathic effect was observed in 37.2% (51/137) samples. It was also possible to identify 40.9% (56/137), between isolated (n?=?46) and nonisolated (n?=?10). Enterovirus serotype diversity (n?=?25) was identified in this study, with the predominant species being B (80.3%), followed by C (16.1%) and A (3.6%). Cases of reinfection by different serotypes were also observed in the three children studied. Analyses involving different age groups of these minors confirmed that the most affected age was between 12 to 24 months, with a prevalence of 77.6% (52/67). The enterovirus (EV) circulated in the 3 years of research, showed peaks in some months, without defined seasonality. This study demonstrated a high circulation and serotype diversity of EV in fecal samples, collected over 30 years ago. This endorsed the evaluation of important points of the epidemiology of these viruses, such as the presence of coinfection and reinfection of the same individual by different circulating serotypes. Understanding the frequency and duration of EV infections is important in determining their association with persistent diarrhea.